Clinical effect of a modified superficial temporal artery-middle cerebral artery bypass surgery in Moyamoya disease treatment - Lu, Liang; Huang, Yimin; Han, Yang; Li, Yu; Wan, Xueyan; Chen, Juan; Zhang, Xincheng; Shu, Kai; Lei, Ting; Wang, Sheng; Gan, Chao; Zhang, Huaqiu (Frontiers in Neurology, 2023)
Background Cerebral extracranial-intracranial (EC-IC) revascularization technique (superficial temporal artery-middle cerebral artery (STA-MCA) bypass grafting) has become the preferred surgical method for the treatment of Moyamoya disease (MMD). We attempted to completely free the two branches of the superficial temporal artery without disconnection. Extracranial and intracranial blood flow reconstruction were then modified by selectively performing a direct bypass technique on one branch and a patch fusion technique on the other of the STA based on the blood flow and the vascular diameter of the intracranial surface blood vessels. Methods A series of modified STA-MCA bypass surgeries performed consecutively between March 2022 and March 2023 were reviewed and compared to conventional combined bypass surgeries performed during the same period. The following information was collected from all enrolled patients: demographic characteristics, clinical symptoms, and preoperative and postoperative imaging, including Suzuki stage and Matsushima grade. The modified Rankin scale (mRS) was used to assess the changes in neurological status before and after surgery. Results A total of 41 patients with Moyamoya disease (MMD) who underwent cerebral revascularization were included in this study, of which 30 were conventional revascularization and 11 were modified revascularization. The mean age was 49.91 years, and 18 (43.9%) of the patients were women. The modified group had a lower incidence of cerebral hyperperfusion syndrome (18.2%) than the conventional group (23.3%). After at least 3 months of follow-up, the bypass patency rate remained 100% in the modified group and 93.3% in the conventional group. All patients in the modified group achieved a better Matsushima grade (A + B), with six (54.5%) having an A and five (45.5%) having a B. In contrast, four patients (13.3%) in the conventional group had a Matsushima grade of C. In all, 72.8% of the modified group had postoperative mRS scores of 0 and 1, which was higher than that of the traditional group (63.3%). Conclusion The improved STA-MCA bypass could provide blood flow to multiple cerebral ischemic areas, reduce excessive blood perfusion, and ensure blood supply to the scalp, with lower complications and better clinical benefits than the traditional combined bypass.